VUV-Spectroscopy of the Plasma Light Emission Generated by the Pulsed Arc Cluster Ion Source (PACIS) - Seeger, K.; Köller, Lars; Tiggesbäumker, J.; Meiwes-Broer, Karl-Heinz (The European physical journal : D, Atomic, molecular, optical and plasma physics)
A pinhole grid spectrometer is used to measure the light emission from the plasma of the pulsed arc cluster ion source (PACIS). Spectra of various metals and carbon have been measured between 20 and 100 nm. In the case of carbon the average electron temperature is estimated to about 0.69 eV. Higher temperatures up to 0.79 eV are measured when inserting seeding gas which flushes the discharge volume with approx. one atmosphere of helium. An operation under this source conditions leads to the generation of an intense charged cluster beam. The application of the source as a bright light source in the VUV region is discussed.